PERTUMBUHAN TANAMAN BONGA KANA (Canna indica L) DALAM MENYERAP LIMBAH DETERJEN PADA BERBAGAI JENIS TANAH - HUTUBESSY, JOSINA I B; Suarna, I Wayan; ASTARINI, IDA AYU (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 7 No 2 (2012), 2012)
Utilization of detergent in daily life has been widespread due to its effective cleaning features in comparison to ordinary soaps. Detergent has been used by small scale in households and laundry firms, and by large in industries. As detergent utilization increased, its accumulative effects on environment become alarming. he experiment was conducted to determine the effect of detergent on the various in order to investigate the influence of detergent waste on different types of soils and its impacts on growth of Canna flower (Canna indica L.). Experiment was carried out at green house at Animal Science Faculty, University of Udayana. The research was carried out for seven months; from January till July 2012, using Randomized Block Design with two factorial. The first factor is the type of soil consisting of Land P1 = Vertisol soil, P2 = Inceptisol soil and P3 = Andisol soil. Second, detergent waste factor which divided into treatments respectively Lo = control, L1 = 500 ml, L2 1000 ml, L3 = 1500 ml. so that there are 12 combinations of treatments;, Each treatment was replicated three times. The results showed that statistically soil types has high significantly influenced on plant height at 30 Days after planting (DAP), 44 DAP, 58 DAP, 100 DAP; upper plant weight, and dry oven weight, detergent waste pH 30 HST, detergent waste temperature 44 HST, available N and available P. Different soil types also produced significant effects on COD 72 and 86 DAP. depending on different types of soil physical properties of soil pH, soil texture, ability of plant to absorb nutrition Canna flower is able to absorb. Canna flower plant uptake efficiency for Vertisol soils 90%, 68%, 46.66% ; lnceptisol 96,6 %, 78%, 60% ; and soil types Andisol 83%, 53%, 36.66% for detergent waste levels at 500 ml, 1000 ml and 1500 ml. Filtration different types of with soil and flowers kanna can lower the pH detergent wastes, detergents and sewage temperature of COD.
Keywords: Cannajlower (Canna indica L), soil types, detergent waste